Odpowiedzi

Najlepsza Odpowiedź!
2009-11-22T22:19:48+01:00
3(x -11) 3(x+1) 2(2x-5)
---------- = -------- - ----------
4 5 11

3/4(x-11)=3/5(x+1)-2/11(2x-5) /*220
165x-1815=132x+132-80x+200
165x-132x+80x=132+200+1815
113x=2147
x=19

2009-11-22T22:28:44+01:00
3(x-11)/4 = 3(x+1)/5 - 2(2x-5)/11 |×220
165(x-11) = 132(x+1)-40(2x-5)
165x-1815 = 132x-132-80x+200
165x-132x+80x = -132+200+1815
113x = 2147 |÷113
x = 19
2009-11-22T22:34:37+01:00
3(x-11)=3(x+1)-2(2x-5)
4511

3x-33=3x+1-4x-10
4511

3x-3x+4x=1-10+33
4511

4x=24/:4
4511

x=6
4511

6/1*1/4511=6x/4511

to jest raczej dobrze;)